K. Hovnanian's approach to preserving intangible assets after acquisitions - Caligiuri, Paula; Castellano, William G. ([London] : SAGE, 2016)
This case study examines homebuilder K. Hovnanian's approach to acquisitions, with a focus on how the organization retains key intangible assets - such as leaders' knowledge and social capital - of their acquired companies. It introduces learners to the HR and business strategy issues associated with acquisitions. By the end of the case study, students will be able to identify HR's role in retaining intangible assets during a strategic acquisition; understand the challenges to managing acquisitions when retaining key intangible assets is a strategic goal; develop HR strategies and implementation plans to integrate the intangible assets of both organizations; and address key HR challenges during the post-acquisition phase.
Originally Published in: Caligiuri, P. & Castellano, W. (2009). K. Hovnanian's approach to preserving intangible assets after acquisitions. Alexandria, VA: Society for Human Resource Management.
Description based on online resource; title from home page (viewed on May 5, 2016).
Keywords: elektronické knihy; electronic books; Intangible property -- Management -- Case studies; Personnel management -- Case studies; Consolidation and merger of corporations -- Case studies